The variation of productivity and its allocation along a tropical elevation gradient: a whole carbon budget perspective. Issue 3 (21st October 2016) - Malhi, Yadvinder; Girardin, Cécile A. J.; Goldsmith, Gregory R.; Doughty, Christopher E.; Salinas, Norma; Metcalfe, Daniel B.; Huaraca Huasco, Walter; Silva‐Espejo, Javier E.; del Aguilla‐Pasquell, Jhon; Farfán Amézquita, Filio; Aragão, Luiz E. O. C.; Guerrieri, Rossella; et al.
Summary: Why do forest productivity and biomass decline with elevation? To address this question, research to date generally has focused on correlative approaches describing changes in woody growth and biomass with elevation. We present a novel, mechanistic approach to this question by quantifying the autotrophic carbon budget in 16 forest plots along a 3300 m elevation transect in Peru. Low growth rates at high elevations appear primarily driven by low gross primary productivity (GPP), with little shift in either carbon use efficiency (CUE) or allocation of net primary productivity (NPP) between wood, fine roots and canopy. The lack of trend in CUE implies that the proportion of photosynthate allocated to autotrophic respiration is not sensitive to temperature. Rather than a gradual linear decline in productivity, there is some limited but nonconclusive evidence of a sharp transition in NPP between submontane and montane forests, which may be caused by cloud immersion effects within the cloud forest zone. Leaf‐level photosynthetic parameters do not decline with elevation, implying that nutrient limitation does not restrict photosynthesis at high elevations. Our data demonstrate the potential of whole carbon budget perspectives to provide a deeper understanding of controls on ecosystem functioning and carbon cycling. Abstract : See also the Commentary on this article by McDowell & Xu, 214 : 903–904 .